QUALITY ANALYSIS OF INTERNET OF THINGS-BASED INVENTORY AND LENDING SYSTEM USING ISO/IEC 25010 - Mursyidin, Mursyidin; Sadrina, Sadrina; Qadri, Fitrah (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: Learning media as a supporting tool for the teaching and learning process. For its use, it is borrowed from the Academic Division and the study program. Often lost and not properly recorded are problems that are often experienced. Inventory management allows proper recording of assets owned. The availability of well-managed goods ensures timely academic services. This research aims to design a multisensor-based inventory and lending system that can improve the efficiency, transparency, and competitiveness of the organization. the method used is prototype with Evaluation of the prototype interface using heuristic evaluation, system quality testing using ISO 25010. Evaluation results obtained that the Internet of Things-based inventory and lending application has been well designed and meets the heuristic criteria. system quality test results have met stakeholder expectations, especially in terms of innovation and competitive advantage and provide satisfaction to users.            Keywords: inventory and lending system; ISO 25010; internet of things  Abstrak: Media pembelajaran sebagai alat pendukung terjadinya proses belajar mengajar. Untuk penggunaannya meminjam pakai dari Bidang Akademik maupun program studi. Sering hilang dan tidak tercatat dengan baik menjadi permasalahan yang sering di alami. Pengelolaan inventaris memungkinkan pencatatan yang tepat terhadap aset yang dimiliki. Ketersediaan barang yang terkelola dengan baik memastikan pelayanan akademik yang tepat waktu. Penelitian ini bertujuan untuk merancang sistem inventaris dan peminjaman barang berbasis multisensor yang dapat meningkatkan efisiensi, transparansi, dan daya saing organisasi. metode yang digunakan adalah prototype dengan Evaluasi antarmuka prototype menggunakan evaluasi heuristic, pengujian kualitas sistem menggunakan ISO 25010. Hasil evaluasi Evaluasi didapat bahwa aplikasi inventaris dan peminjaman barang berbasis Internet of Things telah dirancang dengan baik dan memenuhi kriteria-kriteria heuristic. hasil uji kualitas sistem telah memenuhi harapan stakeholder, terutama dalam hal inovasi dan keunggulan kompetitif serta memberikan kepuasan kepada pengguna. Kata kunci: sistem inventaris dan peminjman; ISO 25010; internet of things